Dari Kampus ke Negeri Sakura: Pemberdayaan Mahasiswa melalui Webinar Edukasi Ketenagakerjaan dan Budaya Kerja di Jepang - Frichicilia Grace Stahlumb; Bilqis Oktaviani Putri; Teddy Chrisprimanata Putra; Sarah Novianti; Ivandra Solihin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Japan faces demographic challenges such as an aging population and a labor shortage, while Indonesia possesses a demographic bonus that has not yet been fully absorbed into the domestic labor market. These conditions create opportunities for employment cooperation between the two countries. However, students still encounter gaps in understanding regarding immigration regulations, academic preparedness, and cultural adaptation to Japan’s work environment. This activity, titled